Testing the impacts of wildfire on hydrological and sediment response using the OpenLISEM model. Part 2: Analyzing the effects of storm return period and extreme events - Wu, Jinfeng (2021)
Wildfires can have strong negative effects on soil and water resources, especially in headwater areas. The spatially explicit OpenLISEM model was applied to a burned catchment in southern Portugal to quantify the individual and combined impacts of wildfire and rainfall on hydrological and erosion processes. The companion paper has calibrated and assessed model performance in this area before and after a fire. In this study, the model was applied with design storms of six different return periods (0.2, 0.5, 1, 2, 5, and 10 years) to simulate and evaluate pre- and post-wildfire hydrological and erosion responses at the catchment scale. Our results show that rainfall amount and intensity played a more important role than fire occurrence in the catchment discharge and sediment yields. Fire occurrence was found to be an important factor for peak discharge, indicating that high post-fire hydro-sedimentary responses are frequently related to extreme rainfall events. The results also suggest a partial shift from runoff to splash erosion after fire, especially for higher return periods. This can be explained by increased splash erosion in burned upstream areas saturating the sediment transport capacity of surface runoff, limiting runoff erosion in downstream areas. Therefore, the pre-fire erosion risk in the croplands of this catchment was partly shifted to a post-fire erosion risk in upper slope forest and natural areas, especially for storms with lower return periods, although erosion risks in croplands were important both before and after fires. These findings have significant implications to identify areas for post-wildfire stabilization and rehabilitation, which is particularly important given the predicted increase in the occurrence of fires and extreme rainfall events with climate change.